Analysis of incidence and prevalence of the respiratory system diseases of the adult population of Moscow and the Russian Federation - V. M. Kuraeva; S. I. Feiginova; А. М. Podchernina (Здоровье мегаполиса, 2022)
Introduction. As a result of the COVID-19 pandemic that swept the whole world in 2020, the level and structure of morbidity changed, the “center of gravity” of adult mortality shifted towards infectious diseases. The anti-epidemic reorientation of healthcare systems in the world has had a negative impact on the health of patients with non-communicable diseases (NCDs). As a result, the morbidity of the adult population, in particular respiratory diseases related to the most important NCDs, becomes particularly relevant in the conditions of epidemiological restrictions in Moscow with the spread of the COVID-19 and the increased burden on the Healthcare system of Moscow.Purpose. The purpose of this study is the analysis of indicators of incidence and prevalence of the respiratory system diseases of the adult population of Moscow and the Russian Federation for the periods 2015–2019 and 2019–2020.Methods and materials. The study used data of the official statistics of the Ministry of Health of the Russian Federation of the “Morbidity of the Russian population” (incidence and prevalence by the care seeking data) for 2015–2020, by the ICD-10 chapter X “Diseases of the respiratory system” (J00-J99), blocks “Chronic lower respiratory diseases” (J40-J47): Asthma, Status asthmaticus (J45, J46); Other chronic obstructive pulmonary disease (J44); chronic bronchitis, Emphysema (J40-J43).Results. The respiratory system diseases continue to occupy leading positions in the structure of morbidity of the adult population of Moscow and the Russian Federation. In the structure of the prevalence of the adult population of Moscow in 2020, respiratory system diseases accounted for 16.8 % (in 2015 – 15.1 %), which is lower than in the whole of the Russian Federation – 17.7 % (2015 – 13.8 %). In the structure of the incidence of the adult population of Moscow was 33.8% (in 2015 – 33.5 %), which is lower than in the whole of the Russian Federation, amounting to 36.9 % (2015 – 28.2 %).The prevalence the respiratory system diseases of the adult population of respiratory system diseases in 2020 in Moscow was 20 830.8 per 100 000 population, which is 19.6 % lower than in the whole of the Russian Federation (25 910.0). Over the period 2015–2019, the indicator of prevalence tended to increase in Moscow by 10.2 %, in the Russian Federation – by 6.2 %. For the period 2019–2020 in Moscow, the increase was only 5.4 %, in the Russian Federation there were higher growth rates (+21.9 %).The incidence the respiratory system diseases in 2020 in Moscow was 15,832.1 per 100 000 population, which is 1.3 times lower than the national average (21,376.0). Over the period 2015–2019, the incidence rate decreased in Moscow by 7.9 %, in the Russian Federation – by 6.6 %. In 2019–2020, the growth rate in Moscow was 4.8 %, in general, a higher increase of 29.7 % was recorded in the Russian Federation.For the period from 2015 to 2019 and during the period of “COVID-19 lockdowns” in 2020, mainly in Moscow, there are high rates of increase in the incidence of chronic obstructive pulmonary disease and asthma. At the same time, a decrease in the level of prevalence and incidence of chronic bronchitis and emphysema was registered both in Moscow and in the Russia.Conclusions. Thus, the morbidity of the adult population the diseases of respiratory system in Moscow tends to decrease, while in the Russian Federation to increase, which requires additional research to find cause-and-effect relationships.